Problematika Mahasiswa STIQ Rakha Amuntai dalam Mengikuti Program Remedial Bahasa Arab (AL-I’ROBY: Jurnal Pendidikan Bahasa Arab Dan Kebahasaaraban, 2024)
The purpose of this study, namely: 1). To describe the problems faced by students who take the STIQ Amuntai Arabic remedial program. 2). To find out what are the supporting factors and inhibiting factors faced by students who take the STIQ Amuntai Arabic remedial program. This study uses descriptive qualitative research. The subjects of this study were teachers, Arabic remedial program supervisors and students who took the remedial program. Data collection techniques used observation, interviews and documentation. While the data analysis techniques used were data reduction techniques, data presentation, and drawing conclusions. The results of this study are that: 1) the problems faced by students who take the Arabic remedial program are: (a) school educational background, (b) limited time to carry out the Arabic remedial program, (c) books taught (d) teacher or lecturer competence. 2) Things that are supporting factors for students who take the Arabic remedial program: (a) students' high interest in Arabic, (b) appropriate learning methods, (c) qualified teachers, (d) and curriculum. The inhibiting factors are: (a) inadequate learning media (b) facilities and infrastructure.